Analisa Penjualan Produk Oli Dengan Metode Data Mining Asosiasi Algoritma Apriori Pada PT. Mitra Petra Sejahtera - Putri Septiani Azura; M. Safii; Fitri Rizki (LPPM STIKOM Tunas Bangsa, 2021)
Competition in the business world makes business people have to think harder in developing strategies to deal with such competition. Marketing strategy requires a reference so that promotion is right on target, for example by looking for similarities between product items. This research was conducted by applying the association rule a priori algorithm method to the sales transaction dataset, to form a candidate combination between product items. The sales transaction dataset was taken in January to December 2019. In this study, a minimum support value of 25% and a minimum confidence value of 60% were determined with data processing using Microsoft Excel and RapidMiner software. A priori algorithm can produce association rules as a reference in product promotion and decision support in providing product recommendations to consumers based on the specified minimum support and confidence values.